Kajian Eksperimental Koefisien Redaman Akustik Bahan Pelapis Plat Dek Kapal - Wibowo Harso Nugroho; Nanang J H Purnomo; Hardi Zen; Andi Rahmadiansah (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2018)
With the increasingly strict requirements of the ship classification bureau for permissible noise limits to allow passengers and crew to be more comfortable and secure a technical assessment is required to address the characteristics of the noise. A noise beyond the standard allowed in the vessel can be a problem to the ship operators. This noise problem will greatly affects the crews' comfort and passengers. One method to reduce the noise on a ship is to use sound insulation. This paper describes the method for determining the absorption coefficient α and the transmission loss (TL) through an acoustic test of a concrete insulation in the laboratory. The test was conducted by using the method of impedance tube where a speciment response measured by a microphone. In general, the properties of this insulation material remains as the main base material which is concrete. it has been found that the transmission loss value (TL) is in the range of 10 - 50 dB whereas for the base material the concrete is around 22 - 49 dB but the absorption coefficient α of the specimen material is much higher than the material of the base material especially in high frequency, which ranges from 0.15 to 0.97, whereas for concrete base materials have absorbent coefficient α ranges from 0.01 to 0.02.